The development of the Antarctic ice shelves during the period 1770-1950 based on expedition maps (Netherlands Polar Data Center (NPDC))
Since about 1773 when the British captain James Cook first crossed the Antarctic Circle a vast amount of scientific data on conditions around Antarctica have been collected. Many of these data originate from the hundreds of Antarctic expeditions of exploration and commerce that have taken place. The data exist largely in the form of maps, charts and logbooks, a large number of which not only contain data about new discoveries of land, but also about the extent of ice shelves and the occurrence of sea ice and ice-bergs in the Antarctic seas. Detailed records of ice limits were kept because ice posed a great danger to the ships and prevented whalers and seal hunters from reaching their hunting grounds. At the present time, a great deal of research is being carried out into the dynamics of Antarctic ice, both causes and consequences. However, it was not until the 1950's that the systematic and long-term recording of meteorological data and ice conditions in the Antarctic region really started. This period is too short to reliably detect changes and trends in ice extent around Antarctica. By studying old maps and logs, however, the period for which data is available can be significantly extended. Although scattered in time, information from historic maps can provide valuable insight in how the present ice situation around Antarctica compares to the situation from 1800 onward. The information collected under this project is being used to compile an integrated digital dataset. Spatial information is stored and analyzed in a Geographical Information System (GIS), facilitating the systematic comparison of map data. Information from logbooks and journals are compiled in a database and linked to geographic locations or features. In this way, an overview of the dynamics of the edges of the Antarctic floating ice over the study period is being created. In this study, data covering Antarctica as a whole will be taken into account. The main focus, however, is on the Weddell Sea (Ronne and Larsen Ice Shelves) and on the Ross Sea (Ross Ice Shelf). Because of their relatively good accessibility, these areas were frequently visited and charted during commercial and scientific expeditions.